Aktivitas Insektisida Ekstrak Air Campuran Buah Piper aduncum dan Daun Tephrosia vogelii terhadap Crocidolomia pavonana Fabricius (Lepidoptera: Crambidae): english - Afriyanita, Afriyanita; Lina, Eka Candra; Darnetty, Darnetty (Jurnal Proteksi Tanaman (Journal of Plant Protection), 2019)
The botanical insecticide is alternative pest control that is feasible to be developed. The inflorescences extract of Piper aduncum and leaf extract of Tephrosia vogelii are known to have insecticidal activity. The study aimed to determine the effect of a mixture of water extract of P. aduncum inflorescences and T. vogelii leaves on C. pavonana. This test used a completely randomized design (CRD) consisting of 6 treatments (0.0, 2.5, 3.0, 3.5, 4.0 and 5.0%) and 5 replications. Observation parameters were larval mortality, antifeedant effect, larval development time, pupal development time, normal and abnormal pupae, and sex ratio. The mixture of water extract of P. aduncum inflorescences and T. vogelii leaves (2:1) at LC50 (3.19%) was antagonistic and at LC95 (6.07%) was additive. The mixture influenced larval mortality (81.0%), had antifeedant effect (84.5%) and prolonged larval development time 1.71 days on 2nd-3rd instars and 2.4 days on 2nd-4th instars compared to control, but there were no effect on pupal development time, number of abnormal pupae and sex ratio.